Uji Coba Empat Varietas Kedelai di Kawasan Pesisir Berbasis Biokompos - Bertham, Yudhi Harini; Aini, Nur; Murcitro, Bambang Gonggo; Nusantara, Abimanyu Dipo (Biogenesis: Jurnal Ilmiah Biologi, 2018)
This study aims to obtain soybean varieties that are able to grow well and produce high in biocomposite coastal areas. This study was compiled using Randomized Block Design (RAKL) with single factor consisting of four varieties of soybeans namely Wilis, Grobogan, Detam I and Detam II. The results showed that the varieties of Wilis produce the highest plant height 63,13 cm, the highest percentage of pods per plant is 91,12%, the highest number of seeds per plant is 249,56 pieces, the heaviest seed weight per plant is 30,92 gram, while the Grobogan which produce the heaviest dry weight is 7,92 g, the highest K absorption is 0,22 g and the highest 100 seed weight is 18,00 g. Thus, the varieties of Wilis and Grobogan have higher adaptation rates than the Detam 1 and Detam II varieties, which has the potential to be developed in coastal areas.